Der Erwerb der Schreibkompetenz im Deutsch als Fremdsprache – zwischen Konzepten und Modellen - Kosevski Puljić, Brigita (Glottodidactica, 2009)
The common issue of writing concepts is modelling of the processes which can increase the ability of acquiring the writing competence. It is necessary to consider different aspects included in the process of acquiring the writing ability: cognitive, communicative, language productive, language receptive, language reflexive, rational and emotional aspects.